FIAT MONEY DALAM PERSPEKTIF EKONOMI DAN HUKUM ISLAM - Kalsum, Ummi (al-'adalah, 2014)
Abstract: Fiat Money in Perspective Economics and Islamic Law. There is a difference of opinion among jurists in the legal status of fiat money that is practiced today. Some scholars assert that the currency should be based on gold and silver or monetary standard should be gold and silver, which is determined based on syar’i. Thus, the fiat money system adopted today in Islam should not be. This opinion was an inspiration for contemporary Islamic economic thinkers who initiated the return of the application of gold-based currency and silver (dinars and dirhams). Opinion of some other scholars, support the permissibility of use currencies other than the dinar and dirham as defined not by Shar’ie but based on the ‘urf. To minimize the economic impact of fiat money, the expected use of foreign currency reduced to a minimum.Keywords: fiat money, Islamic law, Islamic economicsAbstrak: Fiat Money dalam Perspektif Ekonomi dan Hukum Islam. Ada perbedaan pendapat di antara fuqahâ dalam memandang status hukum fiat money yang dipraktekkan saat ini. Sebagian ulama menyatakan bahwa mata uang harus berbasis emas dan perak atau standar moneternya harus berupa emas dan perak, yang ditetapkan berdasarkan syar’i. Sehingga, sistem fiat money yang dianut sekarang ini dalam Islam tidak boleh. Pendapat ini merupakan inspirasi bagi pemikir ekonomi Islam kontemporer yang menggagas kembalinya penerapan mata uang yang berbasis emas dan perak (dinar dan dirham). Pendapat sebagian ulama lain, mendukung pembolehan penggunaan mata uang selain dinar dan dirham karena ditetapkan bukan berdasarkan syar’i tetapi berdasarkan ‘urf. Untuk meminimalisasi dampak ekonomi dari fiat money, diharapkan penggunaan mata uang asing ditekan seminimal mungkin.Kata Kunci: fiat money, hukum Islam, ekonomi Islam